IPTEKS PERLAKUAN AKUNTANSI TERHADAP PENGUKURAN ASET TETAP PADA KANTOR LURAH KLEAK - Ipu, Reinhard Valen; Pinatik, Sherly (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Fixed assets are tangible assets owned by the company or agency in question not for sale, but to assist the operational activities of an agency and have a useful life of more than one year. The kleak village office has several supporting factors in conducting operational activities, one of which in the form of office equipment. This study aims to determine wherher the village office has measured fixed assets based on applicable financial accounting standards. Based on the data that the author obtained it can seen that the village office has not measured fixed assets in accordance with PSAK No. 16.Keywords : Measurement of fixed assets, PSAK No. 16